1999
DOI: 10.2337/diabetes.48.12.2422
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance syndrome in 8-year-old Indian children: small at birth, big at 8 years, or both?

Abstract: We have studied 477 8-year-old Indian children to define the relationship between birth weight and cardiovascular risk factors, including insulin resistance syndrome (IRS) variables and plasma total and LDL cholesterol concentrations. All risk factors were strongly related to current weight. After adjustment for current weight, age, and sex, lower birth weight was associated with higher systolic blood pressure (P = 0.008), fasting plasma insulin and 32-33 split proinsulin concentrations (P = 0.08 and 0.02), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
371
10
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 576 publications
(428 citation statements)
references
References 19 publications
41
371
10
6
Order By: Relevance
“…Evidence that BW affects HOMA%b is inconclusive [12]. There are reports that low BW was associated with elevated HOMA%b [5], whereas others did not found an association [1,2,26]. In our study BW z-score was associated with HOMA%b before and after adjustment for current BMI z-score, but only in Ribeirao Preto.…”
Section: Interpretation Of the Findingscontrasting
confidence: 63%
See 2 more Smart Citations
“…Evidence that BW affects HOMA%b is inconclusive [12]. There are reports that low BW was associated with elevated HOMA%b [5], whereas others did not found an association [1,2,26]. In our study BW z-score was associated with HOMA%b before and after adjustment for current BMI z-score, but only in Ribeirao Preto.…”
Section: Interpretation Of the Findingscontrasting
confidence: 63%
“…There has been some controversy too as to whether the association between birth weight and insulin resistance is linear [1,2], as it was the case in a Pima Indian population [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In four observational studies comprising 3180 children, including an observational study among breastfed children 21, faster postnatal growth measured as the weight gain between birth and two to eight years was positively associated with a higher risk of high BP at the ages of seven to 15 years 21, 44, 48, 49. In contrast, one further study comprising 106 children reported no association between weight gain at birth to 21 years with BP at the age of 21 years.…”
Section: Resultsmentioning
confidence: 97%
“…Babies that are small and thin at birth lack muscle, a deficiency which will persist as the critical period for muscle growth occurs in utero and there is little cell replication after birth [17]. If they develop a high body mass during childhood they can have a disproportionately high fat mass in relation to lean body mass, which will lead to insulin resistance [12,18,19].…”
Section: Discussionmentioning
confidence: 99%